Blockchain Disruption on Management Accountant's Role: Systematic Literature Review - Vecco Suryahadi Saputro; Hamzah Ritchi; Sofik Handoyo (Journal of Accounting Auditing and Business, 2021)
Blockchain considered as an emerging technology that potentially disrupts how management accountant work and his role. This research intends to understand what Blockchain’s capabilities will disrupt the profession by conducting a systematic literature review (SLR). A protocol of SLR is inspired by Kitchenham, Van Akthley, and Okoli in their works. The protocol consists of identifying purpose and outcome research, definition research question, preparing search and review protocol, title and abstract screening, paper quality assessment, data extraction, and data analysis. MAXQDA  was used to conduct the SLR protocol. Seven academic journal databases were used in the searching stage. Kitchenham’s guidelines inspire data extraction and narrative synthesis. This study finds that Blockchain enables the user to do real-time accounting, gather data for supervising and monitoring function, and streamline the accounting practice process. With these findings, the management accountant can prepare to blockchain disruption by upgrading his analytics and computation skills.